(untitled) (ETIMA, 2025)
Ensuring secure and reliable communication between Unmanned Aerial Vehicles (UAVs) and Tactical Operations Centers (TOCs) is critical for mission success in military and emergency response operations. Traditional UAV-to-TOC communication frameworks often suffer from vulnerabilities, including electronic warfare threats, cyberattacks, bandwidth limitations, and interoperability constraints. This paper proposes a Secure Communication Framework for UAV-to-TOC Operations (SCF-UAVTOC) designed to enhance resilience, security, and efficiency in hostile and high-risk environments. The framework integrates end-to-end encryption, blockchain-based authentication, and adaptive frequency management to mitigate jamming and signal interception risks. Additionally, software-defined radios (SDR) optimize spectrum utilization, ensuring reliable communication even in contested environments. To counter cyber threats, intrusion detection systems (IDS) powered by real-time AI monitoring are incorporated, enabling proactive threat mitigation. Furthermore, the framework ensures multi-protocol interoperability, allowing seamless integration of UAV systems within joint military and emergency response operations. The effectiveness of the SCF-UAVTOC model is validated through comparative analysis and simulation-based testing, demonstrating superior performance in secure data transmission, resilience to electronic warfare, and adaptability to dynamic operational conditions. By adopting this framework, defense organizations and emergency agencies can significantly enhance UAV communication security, mission reliability, and overall operational effectiveness in complex battlefield and disaster scenarios.